2021
DOI: 10.5194/acp-2021-117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Siberian fire smoke in the High-Arctic winter stratosphere observed during MOSAiC 2019–2020

Abstract: Abstract. During the one-year MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate) expedition the German icebreaker Polarstern drifted through the Arctic Ocean ice from October 2019 to May 2020, mainly at latitudes between 85° N and 88.5° N. A multiwavelength polarization Raman lidar was operated aboard the research vessel and continuously monitored aerosol and cloud layers up to 30 km height. The highlight of the lidar measurements was the detection of a persistent, 10 km deep wildf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The stratospheric sulfur aerosol and cirrus reflectance show a strong inverse correlation in 2001-2011 from Moderate Resolution Imaging Spectroradiometer (MODIS) observations (Friberg et al, 2015). From MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate), Ohneiser et al (2021) observed 30 km high aerosol and cloud layers over high altitudes in the northern hemisphere from October 2019 to May 2020 and found out that those cloud layers were generated by the major wildfire events in July and August 2019. Atmospheric aerosol show an impact on the occurrence and variability of ice clouds, while the influence of aerosol on their microphysical properties remains highly uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The stratospheric sulfur aerosol and cirrus reflectance show a strong inverse correlation in 2001-2011 from Moderate Resolution Imaging Spectroradiometer (MODIS) observations (Friberg et al, 2015). From MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate), Ohneiser et al (2021) observed 30 km high aerosol and cloud layers over high altitudes in the northern hemisphere from October 2019 to May 2020 and found out that those cloud layers were generated by the major wildfire events in July and August 2019. Atmospheric aerosol show an impact on the occurrence and variability of ice clouds, while the influence of aerosol on their microphysical properties remains highly uncertain.…”
Section: Introductionmentioning
confidence: 99%